THE LANGUAGE USE OF MULTIETHNIC SOCIETY IN KARANG TALIWANG MATARAM (PENGGUNAAN BAHASA PADA MASYARAKAT MULTIETNIS DI KARANG TALIWANG MATARAM) - Baiq Rismarini Nursaly (UIN Raden Mas Said Surakarta, 2016)
Karang Taliwang is one of regions in the district of Cakranegara, Kota Mataram, West Nusa Tenggara Province. Here live three language communities. They are Sasak, Bali, and Sumbawa. Each of them use their own language to communicate with their community but do code mixing when communicate with other language communities. Their choice of language depends on some factors among other things; domain, place, situation, participant and purpose as said by Fishman,â€ who speak, what language, to whom, when, and to what endâ€.